2017
DOI: 10.1177/1010428317709676
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of NRAGE induces autophagy via AMPK/Ulk1/Atg13 signaling pathway in NSCLC cells

Abstract: NRAGE has been reported to be overexpressed in cancer cells, especially in lung cancer cells. To determine the role of NRAGE in non-small-cell lung cancer cells, we investigated the effects of NRAGE on autophagy in non-small-cell lung cancer cells. Human A549 and H1299 cells were transfected with NRAGE-specific small-interfering RNA. The Cell Counting Kit-8 and plate clone assay showed that downregulation of NRAGE could induce the proliferation in A549 and H1299 cells. In addition, our data suggested that down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
1
3
1
Order By: Relevance
“…Hence, our new finding that MAGED2 inhibits autophagy only under stressed conditions fits well with an important role of MAGED2, which is restricted to stress conditions. In this respect, our findings with MAGED2 differ from previous studies showing induction of autophagy upon deletion of MAGEA3/A6 in unstressed HeLa and U2OS cells [15], or unstressed MAGED1-depleted A549 and H1299 cells [32]. Given that activation of the cAMP/PKA pathway by forskolin abrogated autophagy in cells exposed to either physical hypoxia or the ER-stressor tunicamycin indicates that the latter stressor (like hypoxia) may also promote endocytosis of Gαs.…”
Section: Discussioncontrasting
confidence: 94%
“…Hence, our new finding that MAGED2 inhibits autophagy only under stressed conditions fits well with an important role of MAGED2, which is restricted to stress conditions. In this respect, our findings with MAGED2 differ from previous studies showing induction of autophagy upon deletion of MAGEA3/A6 in unstressed HeLa and U2OS cells [15], or unstressed MAGED1-depleted A549 and H1299 cells [32]. Given that activation of the cAMP/PKA pathway by forskolin abrogated autophagy in cells exposed to either physical hypoxia or the ER-stressor tunicamycin indicates that the latter stressor (like hypoxia) may also promote endocytosis of Gαs.…”
Section: Discussioncontrasting
confidence: 94%
“…Chung et al found that the Beclin1 played an important role in RANKL‐induced osteoclastogenesis in BMM, and Atg5 was also required for the ruffled border (Chung et al., 2014; Pierrefite‐Carle, Santucci‐Darmanin, Breuil, Camuzard, & Carle, 2015). More importantly, similar to the NRAGE regulated autophagy in lung cancer cells (Zhou et al., 2017), the present study demonstrated mRNA expression of atg5, atg7, atg12, and beclin1 in NRAGE−/− mice is significantly higher compared to WT mice at control, 2, and 4 weeks. The protein expression of ATG5 and ATG7 exhibited similar changes (Figure 5).…”
Section: Discussionsupporting
confidence: 86%
“…As a form of type-II programmed cell death, autophagy could lead to cell death through lysosome-related degradation (1,13), which associated with tumorigenesis and cancer cell metabolism in recent literatures (14,15). Inducing cancer cell autophagy could be as a potential strategy to evoke cell death.…”
Section: Introductionmentioning
confidence: 99%